Optimization of Pectin Extraction Process from Albedo of Citrus Lemon (Citrus limon) Using Ultrasonic Method - Fitry Filianty; Rachma Nur Alifia; Tri Yuliana; Asep Yusuf; Selly Harnesa Putri (Industria: Jurnal Teknologi dan Manajemen Agroindustri)
Pectin is an industrial raw material that can form gels, thickeners, and emulsifiers widely applied in the food and non-food industries. Extracting pectin with citric acid solvent using ultrasonic waves is considered more effective and efficient. This study aimed to obtain an optimization model for the pectin production process to produce maximum pectin yield and obtain the optimized pectin characteristics. This study used the Response Surface Methodology (RSM) as the optimization method with the Central Composite Design (CCD) experimental design with Design Expert 13 software to determine the treatment combination based on time factors and solvent concentration. The treatment combination obtained was 11. The results showed that the maximum pectin yield value was 34.63% at a 7-minute extraction time using the citric acid solvent concentration of 20% and a validation value accuracy of 99.08%. The optimized pectin characteristics were a water content of 7.66%, ash content of 0.33%, equivalent weight of 183.28 mg, methoxyl content of 7.52%, galacturonic acid content of 67.13%, and degree of esterification of 63.56%. The pectin produced followed the pectin quality standards according to the International Pectin Producers Association (IPPA), except for the equivalent weight.